Social capital and health during pregnancy; an in-depth exploration from rural Sri Lanka - Thilini Chanchala Agampodi; Thilde Rheinländer; Suneth Buddhika Agampodi; Nicholas Glozier; Sisira Siribaddana (BMC, 2017)
Abstract Background Dimensions of social capital relevant to health in pregnancy are sparsely described in the literature. This study explores dimensions of social capital and the mechanisms in which they could affect the health of rural Sri Lankan pregnant women. Methods An exploratory qualitative study of solicited diaries written by pregnant women on their social relationships, diary interviews and in-depth interviews with key informants was conducted. A framework approach for qualitative data analysis was used. Results Pregnant women (41), from eight different communities completed diaries and 38 post-diary interviews. Sixteen key informant interviews were conducted with public health midwives and senior community dwellers. We identified ten cognitive and five structural constructs of social capital relevant to health in pregnancy. Domestic and neighborhood cohesion were the most commonly expressed constructs. Social support was limited to support from close family, friends and public health midwives. A high density of structural social capital was observed in the micro-communities. Membership in local community groups was not common. Four different pathways by which social capital could influence health in pregnancy were identified. These include micro-level cognitive social capital by promoting mental wellbeing; micro-level structural social capital by reducing minor ailments in pregnancy; micro-level social support mechanisms promoting physical and mental wellbeing through psychosocial resources and health systems at each level providing focused maternal care. Conclusion Current tools available may not contain the relevant constructs to capture the unique dimensions of social capital in pregnancy. Social capital can influence health during pregnancy, mainly through improved psychosocial resources generated by social cohesion in micro-communities and by the embedded neighborhood public health services.